Epigenetic mechanisms associated with progression, prognosis, and new treatment strategies for metastatic cervical squamous cell carcinoma - Josué Mondragón-Morales; Rogelio Rogel-Alvarado; Iris Alejandra Noverón-Figueroa; Max Morales-Gutiérrez (Basic & Clinical Cancer Research)
Background: In the 21st century, the main cause of death in both sexes worldwide are cardiovascular diseases, in second place are neoplasms. In the case of women, the fourth cause of mortality is breast cancer despite the screening. Objective: Understanding the epigenetic mechanisms associated with cervical cancer progression and metastasis, considering its correlation with poor prognosis. Methods: To prepare the present article, the search was done on platforms PubMed and Google Scholar, the search was carried out using the following medical subject headings (MeSH) in the search engine: “metastatic cervical cancer”, “cervical cancer epigenetics”, “cervical cancer genetics”, “cervical cancer mirnas”, “cervical cancer lncrnas”, “cervical cancer clinical trials” and “metastatic cervical cancer hpv”, in combination with boolean connectors ‘AND’ and ‘OR’. A total of 114 articles were reviewed, published between 1989 and 2022. Results and conclusions: It is essential to understand and know the epigenetic mechanisms associated with the cervical cancer pathogenesis and progression, to create new targeted treatment schemes for metastatic cervical cancer to reduce the mortality rate and increase disease-free survival.